Epizootological and Epidemiological Place of Sanguivorous Dipterans in a Climate of the Arctic (review) - V. N. Domatskiy; O. A. Fedorova; A. N. Siben (Российский паразитологический журнал, 2020)
The purpose of the research is to analyze epizootological and epidemiological place of sanguivorous dipterans in a climate of the Arctic.Sanguivorous dipterans are widespread at the territory of the Arctic, are the carriers of dangerous animals and human diseases. Factors which promote mass distribution of diseases having vector-borne transmission route are worth of specific attention. Opportunity of insects to travel for a long distance are of great importance in spread of diseases. Range of gadflies, mosquitos and black flies flying away can come up to ten kilometers. Relationship between climate changes and extension of some insects’ geographic range to the north at present and in the near-term prospect are real and are monitored in many cases. Monitoring survey of fauna and ecological features of the sanguivorous dipterans of the northern territories is necessary in recent period, because these organisms are very dependent on the state environmental changes and even seemingly insignificant changes in conditions of the temperature and chemical content of soil and water can lead to changes in their species composition, population and displacement of major fenodata. Increase of air temperature, hatching multiplication as well as changing nature of water plants and lowering of salt content of ponds occurs as the result of climate warming that makes them more allowable for evolution of preimaginal developmental stages of sanguivorous dipterans.